A dialética da sexualidade e da educação sexual na formação de docentes - Gomes, Andréa Regina de Carvalho (2016)
The objective of this study was for us to acquaint about the sex education in teachers training in the Colégio Estadual Mário de Andrade Teachers Training Course, in Francisco Beltrão-PR-BR. We seek to understand which guidelines lead (and if they really lead) the pedagogical work of the teachers who form teachers, regarding to sexuality. By means of empirical and bibliographic researches with qualitative nature, we understand the sexuality as a historical product and human praxis dimension. We based our research by the historical and dialectical materialism. The field research is directed to reading documents produced by the federal and state government in the last twenty years, regarding to the analysis categories: contradiction, historicity, mediations, totality, sexuality, teachers training and sexual emancipatory education, for the teachers training from the Teachers Training Course. We also analyzed works, articles, thesis and dissertations about the sexuality in teachers training and did semi-structured interviews with nine teachers from the Colégio Estadual Mário de Andrade Teachers Training Course, in Francisco Beltrão. We diagnosed that the documents and the guidelines on sexuality demands knowledge from the teachers beyond what most of them had on their initial and continuous formation. And the truths that each one brings from their root culture affects deeply in their way of seeing and living the sexuality, as in the way they teach their students. The will to deepen the knowledge about sexuality exists for the major part of these teachers, but the everyday pedagogical structural conditions bump into a number of impediments for that to happen. We glimpsed an emancipatory sexual education, where the autonomy regarding the value and attitudes linked to sexuality allows the teachers to report sexuality repressive situations. However, to accomplish this emancipation it is necessary to connect dialectically the individual and social poles.